Highest Occurring Vascular Plants from Ladakh Provide Wood Anatomical Evidence for a Thermal Limitation of Cell Wall Lignification - Büntgen, Ulf; Jandova, Veronika; Dolezal, Jiri (Plant, cell & environment, 2025)
As an evolutionary achievement of almost all terrestrial plants, lignin biosynthesis is essential for various mechanical and physiological processes. Possible effects of plant cell wall lignification on large-scale vegetation distribution are, however, not yet fully understood. Here, we present double-stained, wood anatomical stem measurements of 207 perennial herbs (Potentilla pamirica Wolf), which were collected between 5550 and 5850 m asl on the north-western Tibetan Plateau in Ladakh, India. We also measured changes in situ root zone and surface air temperatures along the sampling gradient and applied piecewise structural equation models to assess direct and indirect relationships between the age and size of plants, the degree of cell wall lignification in their stems, and the elevation at which they were growing. Based on the world's highest-occurring vascular plants, the Pamir Cinquefoils, we demonstrate that the amount of lignin in the secondary cell walls decreases significantly with increasing elevation (r = -0.73; p < 0.01). Since elevation is a proxy for temperature, our findings suggest a thermal constrain on lignin biosynthesis at the cold range limit of woody plant growth.
Keywords: lignin; Wood; dendrochronology; treeline research; Potentilla; Indie; plant growth; Plant Roots; buněčná stěna; Plant Stems; stonky rostlin; kořeny rostlin; alpine ecology; wood anatomy; Temperature; Altitude; India; dřevo; nadmořská výška; Tibetan Plateau; Cell Wall; Lignin; teplota